2013
DOI: 10.1186/1471-2318-13-76
|View full text |Cite
|
Sign up to set email alerts
|

One-year outcome of frailty indicators and activities of daily living following the randomised controlled trial; “Continuum of care for frail older people”

Abstract: BackgroundThe intervention; “Continuum of Care for Frail Older People”, was designed to create an integrated continuum of care from the hospital emergency department through the hospital and back to the older person’s own home. The aim of this study is to evaluate the effects of the intervention on functional ability in terms of activities of daily living (ADL).MethodsThe study is a non-blinded controlled trial with participants randomised to either the intervention group or a control group with follow-ups at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
112
0
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(121 citation statements)
references
References 41 publications
3
112
0
6
Order By: Relevance
“…The study included patients, aged ≥75 years, being in need of in-hospital treatment and who fulfilled the foundation of frailty according to the recently validated FRESH (FRail Elderly Support research group) screening instrument,12,20,21 ie, two or more of the following criteria: tiredness from a short walk, general fatigue, frequent falls/anticipation of falls, dependence in shopping and three or more visits to the emergency ward during the last 12 months. Patients were excluded if they declined participation in the study, were unable to give informed consent (and it was impossible to obtain informed consent from a relative), were previously defined MÄVA patients (when a patient already had a MÄVA file implying direct access to the MÄVA facilities), or were clearly suited for care at a conventional acute medical care unit due to the severity of his/her acute condition (acute myocardial infarction, acute stroke, sepsis, or other acute life-threatening conditions).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study included patients, aged ≥75 years, being in need of in-hospital treatment and who fulfilled the foundation of frailty according to the recently validated FRESH (FRail Elderly Support research group) screening instrument,12,20,21 ie, two or more of the following criteria: tiredness from a short walk, general fatigue, frequent falls/anticipation of falls, dependence in shopping and three or more visits to the emergency ward during the last 12 months. Patients were excluded if they declined participation in the study, were unable to give informed consent (and it was impossible to obtain informed consent from a relative), were previously defined MÄVA patients (when a patient already had a MÄVA file implying direct access to the MÄVA facilities), or were clearly suited for care at a conventional acute medical care unit due to the severity of his/her acute condition (acute myocardial infarction, acute stroke, sepsis, or other acute life-threatening conditions).…”
Section: Methodsmentioning
confidence: 99%
“…This includes a person-centered approach focusing on the individual’s needs by validated instruments (Table 1). A few clinical studies have indicated that frail elderly patients could benefit from a CGA, in a general elderly care context, as well as under more specific conditions, eg, ortho-geriatric care 1217. Two meta-analyses showed no differences in mortality between patients treated in CGA units and in conventional care units 15,17.…”
Section: Introductionmentioning
confidence: 99%
“…, Eklund et al . ). This was done because we assumed that respondents who declined to continue in our study had deteriorated health.…”
Section: Methodsmentioning
confidence: 97%
“…), as well as frailty and activities of daily living (ADL) (Eklund et al . ). The implementation of the intervention has also been studied, showing positive results on implementation fidelity (Hasson , Hasson et al .…”
Section: Introductionmentioning
confidence: 97%
“…For this area have indicated that treating frailty in older adults is a realistic therapeutic goal. [21][22][23][24] However, it is still hard to determine how effective these types of intervention are and how efficiency can be influenced by other factors, for example, severity of the clinical condition. Another issue requiring clarification is the effectiveness of interventions in terms of drug prescription and changes in analytical parameters.…”
Section: Introductionmentioning
confidence: 99%